A brief history of blood platelets: A personal view - Berndt, Michael; Metharom, Pat; Andrews, R. (2017)
© Springer International Publishing AG 2017. A search on 'platelets' in Pubmed yields more than 100,000 publications indicating both the depth and interest. Platelets are small anucleate cells that circulate freely in the vasculature. In haemostasis, they adhere rapidly, become activated, spread and coat the damaged vasculature. Our understanding of platelet structure and function has advanced in waves, dependent upon the development of the next cutting-edge technology. This brief chapter describes the key historical events leading to our current understanding of platelet structure and function.